أهمية ألفية ابن مالك وميزاتها في التراث الإسلامي = The importance of Alfiyyah Ibn Mālik and its previllages in Islamic classical literature - Ali, Asem Shehadeh Saleh; Aljamus, Abdullah Mahmud; Ismail, Yasir (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2019)
"الخلاصة الألفية" لجمال الدين محمد بن عبدالله بن مالك الطائي الجيَّاني المتوفى سنة 672هـ، من أشهر المنظومات النحوية وأكثرها انتشاراً بين العلماء وطلبة العلم، وذلك لما لِصاحبها - ابن مالك- من مكانة مرموقة بين العلماء، فقد كانوا يُجلّونه لِعِلمه وسعة اطّلاعه، فقد كان إماماً في كثير من الفنون؛ في القراءات والحديث الشريف واللغة والنحو والصرف وأشعار العرب والفقه، ولا شك أن هذا الاهتمام الشديد بالألفية لم يأت من فراغ؛ بل لما تحمله الألفية من ميزات وخصائص ميّزتها من غيرها، فقد احتوت الألفية على براعةٍ وإبداعٍ في نَظْمِ الأبياتِ، وإبداع في ترتيبِ الأبوابِ وتنسيقِها بشكلٍ غيرِ مسبوق، والسبق في استحداثِ بعضِ المصطَلحاتِ النّحويةِ التي لم تُعرف مِن قبل، ومَزْجِها لمذاهبِ النحويين، وعدمِ التعصّبِ في الآراء والأحكام النَّحويةِ لمذهبٍ معيَّنٍ، وانفرادها بآراءَ لم تُسبق إليها، وقد أثّرت ألفية ابن مالك على نحوٍ واضحٍ في الحركة التّعليمية تأثيراً كبيرا تمَثَّلَ في حركةِ التَّأليفِ المتنوِّعةِ التي كانَ مِنْ ثمرتِها شُروحٌ كثيرةٌ للألفيةِ وحواشٍ متعددةٌ على الشروح، ولأن ابن مالك بنى اختياراته النحوية على قضايا يَراها ويُؤمن بها، كقضيَّةِ الاستشهادِ بالقراءاتِ القرآنيَّةِ الشاذَّةِ، وكقضية الاستشهاد بالحديث الشريف، والاعتمادِ على روايات الحديث في إثبات القواعدِ النحويةِ، فقد رأيناه انفرد باختيارات وآراء لم يسبق إليها؛ جعلت العلماء بعده في صولة مناقشة ما بين مؤيد له ومعارض، ولذلك كله كان لا بد من دراسة ميزات هذه الألفية وبعض خصائصها؛ حيث اتبعت الدراسة المنهج الوصفي التحليلي، وتتبعت كل ما فعله ابن مالك صاحب الألفية وجعل النحاةَ بعده يقتفون أثره ويتتبعون طريقته. *********************************************************** 'The book entitled “Al-Khulāṣah Al-Alfiyyah” by Jamāl al-Dīn Muḥammad bin Abdullah bin Mālik Al-Ṭai Al-Jayāni, who died in 672 AH, is one of the most famous grammatical systems and the most widely distributed among linguists and scholars. This is because the owner of Ibn Mālik has a distinguished position among the scholars. They used to inform him of his knowledge and knowledge. Ibn Mālik was famous in many arts; in the readings, the Hadith, the language, the grammar, the interpretation, the poetry of the Arabs and the jurisprudence. There is no doubt that this great interest in ‘Al-Alfiyyah” did not come from a vacuum; It contains creativity in arranging the unprecedented coordination in the introduction of some grammatical terms that were not previously known, and their mixture of grammatical doctrines, intolerance of the opinions and grammatical rules of a particular doctrine, and their exclusive views that were not preceded by them. Ibn Mālik has clearly influenced the educational movement with a great influence in the diverse composition of the work, which was a fruit of many explanations of “Al-Alfiyyah” and multiple references on the annotations, and because Ibn Mālik built his grammatical choices on issues he sees and believes in, such as quoting the Quranic verses, Prophets Traditions, and rely on the narration of modernity in the proof of grammatical rules. we have seen it alone in the choices and views that have not been made; Linguists have made after the beginning of the discussion between supporters and opponents, and all of this was to be studied features of ‘Al- Alfiyyah”. The study followed the analytical descriptive method, that the Ibn Malik work in ‘Al- Alfiyyah” and his efforts in the grammarians who followed him.